Small family, big impact: In silico analysis of DREB2 transcription factor family in rice. (December 2016) - Herath, Venura
Graphical abstract: Highlights: In this study, five rice DREB2 family members were identified. OsDREB2A, OsDREB2B and OsABI4 are involved in embryo and endosperm development. OsDREB2A, OsDREB2B and OsDREB2C are induced by different abiotic stress conditions. This study will help in understanding the role played by OsDREB2s in rice. Abstract: Dehydration-responsive element- (DREB) proteins are considered as the master regulators of plant abiotic stress responses including drought, salinity and cold. They are also involved in other developmental processes such as embryo and endosperm development. DREB family of transcription factors consist of two sub families namely CBF1/DREB1 and DREB2. In this study, a genome-wide in silico analysis was carried out to dissect the structure and function of DREB2 family transcription factors in the rice genome. Using Arabidopsis DREB2 sequences a total of five rice DREB2 homologs were identified and they were distributed among four chromosomes. All OsDREBs contained the AP2 domain and unique [K/R]GKKGPxN motif characteristic to DREB2 family. During rice growth and development, three OsDREB2 s namely OsDREB2A, OsDREB2B and OsABI4 were expressed and their expression was confined to embryo and endosperm tissues. OsDREB2A, OsDREB2B and OsDREB2C were expressed under abiotic stress conditions. OsDREB2B was expressed under drought, salinity and cold stress conditions while OsDREB2A and OsDREB2C were expressed only under drought and salinity conditions. The putative promoter regions of OsDREB2 s were enriched with elements related to cellular development, hormonal regulation and stress response validating the observed expression dynamics. Co-expression analysis revealed that embryo development and stress related genes were expressed together with OsDREB2 s. Predicted post-translational modifications indicated the fine regulation of OsDREB2s. These findings may shed light in uncovering the complex abiotic stress signaling networks and future genomics studies targeting the development of climate ready crops.